Bhartiya upmandalon mein 1987 ke dauran madhyam evam bheeshm sukha ke kshetriya vistar ka vargikaran (MAUSAM, 2005)
Based on a simple classification, analysis of aerial spread of moderate and severe drought during monsoon season (June – September) of 1987 has been carried out in 33 sub-divisions of India by using the cumulative weekly rainfall departures from the normal. Weather systems responsible for the activity and failure of monsoon have also been described.  In this year, no weather system developed in the monsoon trough from July to September resulting in a very weak activity of monsoon surge.  This was the main reason which led to large scale severe drought over India during 1987.                Widespread and fairly widespread severe drought occurred in maximum 35% and 25% sub-division of the country respectively.  Fairly widespread moderate drought appeared in 20% sub-divisions during tenth, fourteenth and fifteenth week.  Widespread severe drought emerged in Saurashtra and Kutch for a continuous longer duration of 16 weeks whereas fairly widespread moderate drought of longest duration of 10 weeks occurred in Kerala.  The number of sub-divisions affected by moderate and severe drought of isolated category exceeded those under scattered, fairly widespread and widespread categories.